2021
DOI: 10.1038/s41567-021-01290-4
|View full text |Cite
|
Sign up to set email alerts
|

Coherent spin-wave transport in an antiferromagnet

Abstract: Magnonics is a research field complementary to spintronics, in which the quanta of spin waves (magnons) replace electrons as information carriers, promising less energy dissipation 1-3 . The development of ultrafast nanoscale magnonic logic circuits calls for new tools and materials to generate coherent spin waves with frequencies as high, and wavelengths as short, as possible 4,5 . Antiferromagnets can host spin waves at THz frequencies and are therefore seen as a future platform for the fastest and the least… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 48 publications
4
59
0
Order By: Relevance
“…It should be clari ed that the second peak can exist when the coupling energy is large enough to overcome the Zeeman energy of the top Fe 2 O 3 at the valley (ii), otherwise the n (top Fe 2 O 3 ) will maintain spin-op state rather than deviating towards n // H. The magnitude of the second peak is smaller than the rst one can be ascribed to less component of n along x-axis. In contrast, the SMR in inverted sandwich, Fe 2 O 3 (4)/Cr 2 O 3 (4.4)/Fe 2 O 3 (12) (Supplementary Note 7), does not present resistance peak signal before H = 0, demonstrating that the n in the 12 nm-thick Fe 2 O 3 maintains spin-op state rather than deviating towards H at low magnetic eld because of the large Zeeman energy, indicating the existence of the orthogonal coupling.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…It should be clari ed that the second peak can exist when the coupling energy is large enough to overcome the Zeeman energy of the top Fe 2 O 3 at the valley (ii), otherwise the n (top Fe 2 O 3 ) will maintain spin-op state rather than deviating towards n // H. The magnitude of the second peak is smaller than the rst one can be ascribed to less component of n along x-axis. In contrast, the SMR in inverted sandwich, Fe 2 O 3 (4)/Cr 2 O 3 (4.4)/Fe 2 O 3 (12) (Supplementary Note 7), does not present resistance peak signal before H = 0, demonstrating that the n in the 12 nm-thick Fe 2 O 3 maintains spin-op state rather than deviating towards H at low magnetic eld because of the large Zeeman energy, indicating the existence of the orthogonal coupling.…”
Section: Resultsmentioning
confidence: 93%
“…We rst show in Fig. 2a SMR signals of a control sample Fe 2 O 3 (12)/Pt(4) (units in nanometers), where the magnetic eld (H) and current (I) is along x-axis and the spin polarization generated by the spin Hall effect of Pt is along y-axis. As expected, comparatively low resistance states at high magnetic elds re ect that the Néel vector (n) of Fe 2 O 3 is perpendicular to H (I) due to the spin-op at high elds and deviates towards H (I) at low elds, which is quite characteristic for negative SMR of AFM [17][18][19][20] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to overcome this constraint are subject of current research and first promising results have been reported. [9][10][11] In THz spectroscopy, with the aid of ultrafast lasers and advanced detection schemes, dynamical processes in the (sub-) picosecond range become accessible. [12,13] This progress allows not only performing time-resolved studies but enables a control of magnetization dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] Other examples include the coherent generation of magnons. [11] Control over THz-driven spin precession [19][20][21][22] opens the field of THz magnetometry, i.e. the fully optical extraction of magnetic properties.…”
Section: Introductionmentioning
confidence: 99%